Keratoconus: Available Treatment Options - Choksi Twinkle; Saroj Sahdev; Rajendra Pawar (Delhi Journal of Ophthalmology)
Treatment of keratoconus has evolved substantially over years. Treatment modalities are aimed at stabilization of progressive ecstasia with least invasive approach. Mainstay of treatment has shifted from keratoplasty - (penetrating or lamellar) to less invasive techniques like corneal collagen cross linking, intrastromal corneal ring segments and topography-guided PRK. Recently Bowman Layer Transplantation has evolved as a less invasive, promising option in patients with advanced progressive form of disease.